The Hyperpolarization-Activated Cyclic-Nucleotide-Gated Channel Blocker Ivabradine Does Not Prevent Arrhythmias in Catecholaminergic Polymorphic Ventricular Tachycardia - Bueno-Levy, Hanna; Weisbrod, David; Yadin, Dor; Haron-Khun, Shiraz; Peretz, Asher; Hochhauser, Edith; Arad, Michael; Attali, Bernard (Frontiers in Pharmacology, 2020)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited, stressed-provoked ventricular arrhythmia. CPVT is treated by -adrenergic receptor blockers, Na+ channel inhibitors, sympathetic denervation or by implanting a defibrillator. We showed recently that blockers of SK4 Ca2+-activated K+ channels depolarize the maximal diastolic potential, reduce the heart rate and attenuate ventricular arrhythmias in CPVT. The aim of the present study was to examine whether the pacemaker channel inhibitor, ivabradine could demonstrate anti-arrhythmic properties in CPVT like other bradycardic agents used in this disease and to compare them with those of the SK4 channel blocker, TRAM-34. The effects of ivabradine were examined on the arrhythmic beating of human induced pluripotent stem cells derived cardiomyocytes (hIPSC-CMs) from CPVT patients, on sinoatrial node (SAN) calcium transients and on ECG measurements obtained from transgenic mice model of CPVT. Ivabradine did neither prevent the arrhythmic pacing of hIPSC-CMs derived from CPVT patients, nor preclude the aberrant SAN calcium transients. In contrast to TRAM-34, ivabradine was unable to reduce in vivo the ventricular premature complexes and ventricular tachyarrhythmias in transgenic CPVT mice. In conclusion, ivabradine does not exhibit anti-arrhythmic properties in CPVT, which indicates that this blocker cannot be used as a plausible treatment for CPVT ventricular arrhythmias.